Bushell & Macaulary, The Emergence Of Latin America In The Nineteenth Century, Burkholder & Johnson, Colonial Latin America - Cummins, Victoria (Teaching History: A Journal of Methods, 1996)
Since their appearance on the scene four and six years ago, respectively, Burkholder and Johnson’s Colonial Latin America and Bushnell and Macaulay’s The Emergence of Latin America in the George Pullen Nineteenth Century have been widely adopted for course preparation and classroom use.